Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Cumulative Review - Page 565: 43



Work Step by Step

$\frac{3x^{2}+2x}{x-1}-\frac{10x-5}{x-1}$ =$\frac{3x^{2}+2x-(10x-5)}{x-1}$ =$\frac{3x^{2}+2x-10x+5}{x-1}$ =$\frac{3x^{2}-8x+5}{x-1}$ =$\frac{3x^{2}-3x-5x+5}{x-1}$ =$\frac{3x(x-1)-5(x-1)}{x-1}$ =$\frac{(x-1)(3x-5)}{x-1}$ =$3x-5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.